Factors Affecting the Pregnancy Outcome in Patients with Previous One Caesarean Section (Medicine Today, 2014)
This case series study was designed to determine the factors affecting the pregnancy out come in patients with previous one caesarean section. The study was conducted at Marie Stopes Clinic Primium-1 Dhanmondi from July 01, 2012 to January 31, 2013. A total of 150 patients with previous one caesarean section who presented at term were included in the study. The data were collected through proforma and subjected to statistical analysis. Out of 150 patients, 81 (54%) patients had trial of scar and the remaining 69 (46%) patients underwent repeat elective caesarean section. Among those who had trial of scar only 35 (43.2%) patients achieved successful vaginal delivery and remaining 46 (56.8%) had emergency caesarean section. Common indication for repeat emergency caesarean section was non progress of labour (47.8%). It was frequent in women who reported late to hospital after the onset of labour and in women who did not seek antenatal booking in pregnancy. Maternal complications like post partum hemorrhage, scar dehiscence, wound infection and febrile illness were more in those who had emergency caesarean section. There was no maternal mortality in the study. Perinatal outcome was not affected by the mode of delivery. There were two perinatal deaths which occurred in non-booked patients who underwent emergency caesarean section. Most of the women in our study had repeat caesarean section for failed progress. Regular antenatal check up and early report to hospital after the onset of labour can reduce the rate of repeat caesarean section. DOI: http://dx.doi.org/10.3329/medtoday.v26i1.21300 Medicine Today 2014 Vol.26(1): 01-03